ANALYSIS OF THE APPLICATION OF DAGMAR THEORY IN DHILA FOOD'S DIGITAL MARKETING STRATEGY VIA TIKTOK - Ridwan, Elent Praditya; Hariyanto, Didik (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the application of the DAGMAR (Defining Advertising Goals for Measured Advertising Results) theory in the digital marketing strategy of Dhila Food through the TikTok platform. The background of this research is based on the increasing use of social media by SMEs as a promotional tool to expand market reach and build stronger engagement with consumers, with TikTok chosen for its fast content distribution and interactive features. Method: This study uses a qualitative method with data collected through interviews, observations, and documentation. Results: The findings indicate that Dhila Food’s digital marketing strategy can be explained through the five stages of the DAGMAR theory: unaware, awareness, comprehension and image, attitude, and action. Consistent content uploads, the publication of On the Road schedules, live streaming activities, and documentation of customer queues are key factors in raising awareness, strengthening brand image, and fostering positive attitudes, which ultimately lead to purchase actions. Novelty: Thus, the application of DAGMAR in Dhila Food’s digital marketing strategy via TikTok has proven effective in increasing consumer interest and enhancing brand image.